2012
DOI: 10.3390/s121114307
|View full text |Cite
|
Sign up to set email alerts
|

Long Chain N-acyl Homoserine Lactone Production by Enterobacter sp. Isolated from Human Tongue Surfaces

Abstract: We report the isolation of N-acyl homoserine lactone-producing Enterobacter sp. isolate T1-1 from the posterior dorsal surfaces of the tongue of a healthy individual. Spent supernatants extract from Enterobacter sp. isolate T1-1 activated the biosensor Agrobacterium tumefaciens NTL4(pZLR4), suggesting production of long chain AHLs by these isolates. High resolution mass spectrometry analysis of these extracts confirmed that Enterobacter sp. isolate T1-1 produced a long chain N-acyl homoserine lactone, namely N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 28 publications
(39 reference statements)
2
29
0
Order By: Relevance
“…We have also shown that Enterobacter sp. produces C8-HSL and C12-HSL [26]. Similarly, in this work, we showed that strain T2-2 also produced C8-HSL and C12-HSL (Figure 4).…”
Section: Resultssupporting
confidence: 84%
“…We have also shown that Enterobacter sp. produces C8-HSL and C12-HSL [26]. Similarly, in this work, we showed that strain T2-2 also produced C8-HSL and C12-HSL (Figure 4).…”
Section: Resultssupporting
confidence: 84%
“…isolated from chilled salmon and raw milk can produce a detectable amount of AHLs [85,86]. The quorum molecule was confirmed to be C12-HSL by high resolution mass spectrometry in a subsequent dorsal human tongue study [52]. In species that do not produce AHLs, such as E. cloacae GS1, a LuxR homolog, SdiA, has been detected.…”
Section: Quorum Sensing In Gram-negative Bacteriamentioning
confidence: 99%
“…As reported by Angelika and colleagues, E. sakazakii produces 3-oxo-C6-HSL and 3-oxo-C8-HSL, indicating its pathogenicity is achieved via cell-to-cell signaling molecules [33]. Other work done by Yin and colleagues further showed that a member of the Enterobacter genus exhibits long chain AHL production, namely of N -dodecanoyl- l -homoserine lactone (C12-HSL) [34]. The spent culture supernatant of M004 strain was analyzed using mass spectrometry analysis which confirmed the presence of 3-oxo-C6-HSL and 3-oxo-C8-HSL (Figure 3).…”
Section: Resultsmentioning
confidence: 99%